2011
DOI: 10.1590/s0100-06832011000400035
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas de manejo e os estoques de carbono e nitrogênio em latossolo de cerrado com a sucessão soja-milho

Abstract: RESUMOOs estoques de C e N no solo são determinados pelo balanço entre adição e perda no sistema, sendo o preparo do solo e o sistema de culturas determinantes nesse processo. Este estudo teve por objetivo avaliar o efeito de sistemas de manejo do solo baseados em sistemas de preparo, plantas de cobertura e adubação fosfatada nos estoques de C e N em frações físicas da matéria orgânica do solo e na biomassa e respiração microbiana em um solo cultivado por 11 anos na sucessão soja-milho. O experimento foi inici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
3
10
0
2
Order By: Relevance
“…Sousa et al (2010) verified SOC contents at the 0-to 20-cm depth ranging from 14 to 22 g kg −1 due to differences in the inputs of plant residues as a function of P fertilizer applications in annual cropping systems and pastures. Similar results were also reported by Nunes et al (2011).…”
Section: Soil Phosphorus Soil Organic Carbon and Microbial Indicatorssupporting
confidence: 92%
“…Sousa et al (2010) verified SOC contents at the 0-to 20-cm depth ranging from 14 to 22 g kg −1 due to differences in the inputs of plant residues as a function of P fertilizer applications in annual cropping systems and pastures. Similar results were also reported by Nunes et al (2011).…”
Section: Soil Phosphorus Soil Organic Carbon and Microbial Indicatorssupporting
confidence: 92%
“…This may be due to the greater root biomass in the 0.00-0.05 m layer under NT system. Other workers (Souza Nunes et al, 2011) have also reported that the NT system resulted in stratification of SOC, while the MP system resulted in a more homogeneous distribution in the 0.00-0.20 m layer.…”
Section: Changes In Soc Distribution In Soil Profilementioning
confidence: 81%
“…Thus, the soybean, maize/ wheat succession system contributed to increased levels of TC, especially after reaching the maintenance phase (ANGHINONI, 2007). After the maintenance phase of the NT system was reached (ANGHINONI, 2007), non-disturbance of the system, allied with different strata of the root systems of soybean, maize, and wheat, as well as the potential for C accumulation in the root system of the grasses (NUNES et al, 2011;LOSS et al, 2013), increase the total carbon content. In addition, the difference in the total carbon content found in the 0.00-0.05 m layer between the area of 6 years and 22 years since adoption of the NT is due to the stratification of carbon accumulation, as well as the higher root growth of grass species, such as maize, in the uppermost layers of the soil, as also reported by Costa et al (2009).…”
Section: Resultsmentioning
confidence: 99%